SOCIO-ECONOMIC BURDEN IN THE SUSTENANCE OF SANITATION RELATED DISEASES IN EBONYI STATE, SOUTHEAST, NIGERIA (Journal of Biomedical Investigation, 2022)
Background: Sanitation related-diseases have affected millions of people, mostly in developing countries. This study aimed to determine the socioeconomic burden in the sustenance of sanitation related-diseases in Ebonyi State, Nigeria.Materials and Methods: The study was conducted in Ebonyi State, Southeast, Nigeria and adopted a descriptive cross-sectional design; sample size was 461 obtained from primary source. The descriptive statistics of frequency, percentage, mean and standard deviation were used to present the obtained data.Results: Majority (180 or 39%) of the participants reported the size of their household to consist of 3-4 people followed by 150 (33%) who reported having 5-6 people. Out of the 461 participants, 258 (56%) reported that some children within their household had visited health centre due to sanitation-related diseases (such as stomach pains, fever, headache, blood in stool, watery stool), while 219 (48%) paid ₦1,000-₦3,000 for medical services (drugs, nursing services, doctor's services, laboratory services). Also, 294 (64%) reportedly paid less than ₦1,000 for transportation to and from a health facility due to sanitation-related diseases. Also 253 (55%) reported they spent total estimate of ₦1,000-₦5,000 as cost of treatment of sanitation-related diseases. Majority (291 or 55%) spent less than 5 days in a health facility due to sanitation-relateddiseases, 177 (38%) recorded 5-10 days absence from work, and 306 (66.4%) claimed they lost less than ₦1,000 per day because of a child's admission in the health facility. On weekly basis, 300 (65.1%) reported they lost
Keywords: burden; community; sanitation; socio-economic burden; sanitation related diseases